A Rare Case of Splenic Marginal Zone B-Cell Lymphoma Mimicking Relapsing Polychondritis of the Ear - Gary J. Huang; Bryan Mendes; Kianoush Sheykholeslami (Case Reports in Otolaryngology)
Relapsing polychondritis (RPC) is a poorly understood phenomenon associated with cartilaginous inflammation of the ear, nose, tracheobronchial tree, and peripheral joints. Many cases of RPC respond to anti-inflammatories and resolve with no further complications. However, RPC has also been linked to more insidious conditions such as malignancies, autoimmune disorders, vasculitis, or underlying infections. Given the spectrum of associated disorders, patients with RPC may need to be monitored for more insidious underlying conditions. In this case, we report a unique case of bilateral auricular inflammation and nasal inflammation mimicking RPC as the only presenting symptom of splenic marginal zone B-cell lymphoma and we survey related cases in the literature.